6(3-2x)+8x=9

Simple and best practice solution for 6(3-2x)+8x=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3-2x)+8x=9 equation:


Simplifying
6(3 + -2x) + 8x = 9
(3 * 6 + -2x * 6) + 8x = 9
(18 + -12x) + 8x = 9

Combine like terms: -12x + 8x = -4x
18 + -4x = 9

Solving
18 + -4x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -4x = 9 + -18

Combine like terms: 18 + -18 = 0
0 + -4x = 9 + -18
-4x = 9 + -18

Combine like terms: 9 + -18 = -9
-4x = -9

Divide each side by '-4'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| (5y+4)(y+6)=-4(5y+4) | | -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 | | 6x^2+3=5x | | x^2-10x-18=0 | | 3(2x+3)+4=-59 | | 8x-2y=-44 | | 12+(x+3)-3x=117 | | 3(2x+3)+4x=-59 | | c(q)+6000+10qR(q)=12 | | x*x-4=240 | | -84=-15w+9w | | 8(x+2)-2x=4 |

Equations solver categories